Satu dalam Keberagaman: Komunikasi Antar Agama di Kota Palangkaraya - Yunaldi, Ari; Sobirin, Ahmad; Mualimin, Mualimin (NALAR, 2021)
This study aims to describe social harmony between religious communities in Panjehang, Palangkaraya City. This study is qualitative research with a phenomenological approach. Data was obtained by observation, interviews, and documentary studies. The data were then analyzed using interactive qualitative analysis techniques: data reduction, data presentation, and conclusion. This study found that three essential aspects led to inter-religious harmony in Panjehang Village. First, local wisdom is in the form of the inherent Huma Betang philosophy and customs and becomes a guideline in community social interactions. Second, strong family ties. Third, the role of community leaders in bridging community communication so that harmonious social interaction is built. It can be concluded that the dimensions of culture and local wisdom play a crucial role in communication and harmonious social interaction between religious communities.Keywords :